The application of new technology fisheries cultivation for communities in Nelayan Indah sub-district Medan Labuhan district Medan city North Sumatera province (Talenta Publisher, 2019)
The Community Service Program (PPM) aims to empower the community to utilize the potential of aquaculture, namely cages. Fish cultivation in cages is very instrumental in helping to conserve water resources in public waters, because arrests carried out continuously will disrupt the sustainability of these waters (Anonimus, 1996). Providing assistance in facilities and infrastructure in empowering fishing communities and providing capital to strengthen aquaculture businesses. Long-term goals can avoid a famine for fishermen where in the western season fishermen cannot catch fish, improve the quality of life of the community by expanding employment opportunities for fishermen and society in general. Community service was carried out in Kelurahan Nelayan Indah, Medan Labuhan Sub-District, Medan City, North Sumatra Province. To achieve this goal, several stages of activities will be carried out. First is the initial survey activity to find out the condition of the service location and find out how many fishermen have their own pool. The second stage is to socialize the planned activities that will be implemented to empower fishing communities and provide capital to strengthen aquaculture businesses that use new technology. The third stage is improving science and technology using fish cages. This community service program is carried out within 6 months. The target and output of this program are: (1) Improving new knowledge and technology about aquaculture in fishing communities that have pondering. (2) Development of productive and sustainable aquaculture that emphasizes environmentally friendly cultivation practices. (3) Using Floating Net Cages (KJA) which have superior strength, resistance waves and currents. Thus, fish yields of quality, healthy and highly nutritious fish are obtained.